2013
DOI: 10.1242/jeb.093567
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous locomotor activity in late-stage chicken embryos is modified by stretch of leg muscles

Abstract: Chicks initiate bilateral alternating steps several days before hatching and adaptively walk within hours of hatching, but emergence of precocious walking skills is not well understood. One of our aims was to determine whether interactions between environment and movement experience prior to hatching are instrumental in establishing precocious motor skills. However, physiological evidence of proprioceptor development in the chick has yet to be established; thus, one goal of this study was to determine when in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…It is possible that this is a normal trend that occurs at this late stage but is perhaps more likely due to constriction of movement by the large size of the embryo relative to the egg size at late developmental stages. Indeed, late-stage embryos have been observed to extend their limbs beyond the egg and exhibit more frequent limb movements if sections of shell adjacent to the limbs are removed (Bradley et al 2014). It is possible that this restraint may act to limit the ability of embryos to respond with an increase in motility to an external stimulus such as light.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that this is a normal trend that occurs at this late stage but is perhaps more likely due to constriction of movement by the large size of the embryo relative to the egg size at late developmental stages. Indeed, late-stage embryos have been observed to extend their limbs beyond the egg and exhibit more frequent limb movements if sections of shell adjacent to the limbs are removed (Bradley et al 2014). It is possible that this restraint may act to limit the ability of embryos to respond with an increase in motility to an external stimulus such as light.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many sequences, one muscle was consistently active, and the antagonist muscle failed to produce one or more bursts. EMG bursts were detected and analyzed based on previously established criteria (Bradley et al, 2008;Bradley, Ryu, & Yeseta, 2014;Ryu & Bradley, 2009;Sindhurakar & Bradley, 2012 five rhythmic bursts, and the right TA (r-TA) failed to produce bursts during three of the RLM cycles (asterisks). For example, in Figure 2B, the hip flexor (SA) produced 11 bursts (10 cycles), and its antagonist (CF) failed to produce bursts that met detection criteria in four cycles (noted by asterisks).…”
Section: General Features Of Rlm Emgmentioning
confidence: 99%
“…In chick embryos, the flexed posture of the neck, spine, wings, and legs becomes progressively more extreme in the final week before hatching (plates 1-3, Hamburger & Oppenheim, 1967). Kinematic study of RLMs in ovo indicated that at E20, hip, knee, and ankle excursions averaged 3°, compared to an average of approximately 8°at E18 (Bradley et al, 2014) and almost 50°at E12 (Bradley, Solanki, & Zhao, 2005). This flexed posture may be mechanically imposed by spatial constraints, as when the embryo or fetus begins to outgrow the volume of the prenatal environment and there is no longer room to extend the limbs.…”
Section: Significance Of Flexor Bias During Developmentmentioning
confidence: 99%
“…Isolated spinal locomotor networks exhibit flexor‐biased organization in the neonatal mouse (Dougherty et al, ; Endo & Kiehn, ; Machado, Pnevmatikakis, Paninski, Jessell, & Miri, ). Further, imposed changes in muscle length can alter RLM EMG in chicks 1 to 3 days prior to hatching (Bradley, Ryu, & Yeseta, ). Though isolated spinal circuits produce a flexor bias during fictive locomotion, it appears that the mechanisms for flexor bias have not been examined in a neurologically intact embryo or fetus under normal late‐stage prenatal conditions that precede postnatal locomotor behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In neurologically intact chick embryos, sensory input can alter RLM muscle activity by E20. For example, restraint‐induced stretch of ankle flexors increased RLM flexor burst amplitude (Bradley et al, ). During restraint, flexor RLM bursts were enhanced, but EMG was quiescent between bursts and consecutive RLMs, suggesting descending fusimotor drive may have contributed to the phasic response.…”
Section: Introductionmentioning
confidence: 99%